Study of Urban Spatial Inequality in Tehran (1996 to 2011) - Gholamreza Latifi; Mojdeh Babagoli (برنامه‌ریزی توسعه شهری و منطقه‌ای, 2015)
This research examines the urban spatial inequality in Tehran. For thispurpose, distribution of economic, social and space desirability indices andthe relationships among them were studied. These indices will be calculatedwith secondary analysis of detailed results of Iran National Population andHousing and reports on price of land and rental price of residential buildingsin 1996, 2006 and 2011 based on Morris Level Processing. These resultsindicate that the distribution of the space desirability index has significantrelationships with the distribution of social and economic indices as theserelationships are confirmed in all three census. Although the distributions ofeconomic and social indices become more balanced over the 15 years,significant change doesn’t occur in the distribution of space desirabilityindex. In contrast, in 1996, 2006 and 2011, the correlation between socialindex and space desirability index exceeds the correlation between economicindex and space desirability index. This indicates the social index’sincreasing of influence on space desirability.